PEMBERDAYAAN KARANG TARUNA DESA PAPRINGAN UNTUK PEMBUATAN PUPUK ORGANIK DARI KOTORAN SAPI - Giftamarini, Rainy; Habsi, Kholifatul; Lestari, Lisa Dwi; Pratiwi, Salsabila Rusdi; Aisy, Inas Rohidatul; Suhadak; Fadhilah, Alifatin; Mulia, Aria Anugerah; Putri, Rani Alja; Najrawati; et al. (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
Papringan village is one of the villages with the highest number of cattle in Banyumas district, Central Java. Waste from livestock, such as manure and leftover feed, has yet to be explicitly managed. The manure is left open so that when it rains, it is carried away by the water flow and pollutes the surrounding environment. The communication results with the head of the livestock group and the head of the Youth Group of Jangkar Mas VIII in Papringan Village showed great hope that they could manage livestock manure in Papringan Village into organic fertilizer. The initial survey conducted on March 31, 2021, through the distribution of Google Forms, showed that 51.4% of youth members had made fertilizer from organic waste, and 73% had made fertilizer from livestock manure. Based on the survey results, most members of the youth organization have made fertilizer from organic waste and livestock manure, so it has the potential to be developed to manage the production and marketing of organic fertilizer from livestock manure. The service activity began with outreach to members of youth organizations and farmer groups and was attended by the Head of Papringan Village. Furthermore, direct practice and assistance in manufacturing organic fertilizers are carried out. Organic fertilizer production uses livestock manure, straw, and fruit waste. Fertilizer production is carried out routinely twice weekly with a production target of 3.5 tons/month. — Desa Papringan merupakan salah satu desa dengan jumlah ternak sapi terbanyak di kabupaten Banyumas, Jawa Tengah. Limbah dari peternakan seperti kotoran ternak dan sisa pakan selama ini belum dikelola secara khusus. Kotoran ternak tersebut dibiarkan terbuka sehingga ketika hujan terbawa aliran air dan mencemari lingkungan sekitar. Hasil komunikasi dengan ketua kelompok ternak dan ketua karang taruna Jangkar Mas VIII Desa Papringan menunjukkan besar harapan mereka dapat mengelola kotoran ternak di Desa Papringan menjadi pupuk organik. Survei awal yang dilakukan pada 31 Maret 2021 melalui penyebaran Google Form diperoleh hasil sebanyak 51,4% anggota karang taruna pernah membuat pupuk dari sampah organik dan 73% pernah membuat pupuk dari kotoran ternak. Berdasarkan hasil survei sebagian besar anggota karang taruna pernah membuat pupuk dari sampah organik dan kotoran ternak, sehingga berpotensi dikembangkan mengelola produksi dan pemasaran pupuk organik dari kotoran ternak. Kegiatan pengabdian diawali dengan penyuluhan kepada anggota karang taruna, kelompok peternak serta dihadiri Kepala Desa Papringan. Selanjutnya dilakukan pendampingan pembuatan pupuk organik. Produksi pupuk organik dilakukan dengan menggunakan bahan kotoran ternak, jerami serta limbah buah. Tujuan pengabdian untuk mengurangi limbah kotoran ternak serta untuk memberikan pengalaman kepada karang taruna mengelola limbah kotoran ternak menjadi pupuk organik.